Sedentary Behavior of Elementary School Children According to the Perception of Class Teachers and Physical Education Teachers - Syamsul Arif Hidayatulloh Akhsan; Susilo Bekti; Adi Sucipto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
With the development of technology, it indirectly changes the lifestyle to be more lazy to do physical activity, especially for elementary school children. The method in this study is to use a quantitative approach with a comparative causal method where it is done by comparing the perceptions of class teachers and Physical Educationto determine the sedentary behavior of elementary school students spread across cities and districts in East Java. Respondents in this study totaled 78 teachers, of which 43 were class teachers and 35 were physical education teachers. Data were collected through questionnaires via google form with 5 Likert answer scales and analyzed with one sample t-test and independent sample t-test. The results of the study are: 1) Physical activity of elementary school children according to class teachers has not met the adequate criteria set. 2) Physical activity of elementary school children according to Physical Educationhas not met the adequate criteria set. It can be concluded in this study that the physical activity of elementary school children according to physical education teachers has not met the established adequacy criteria. Meanwhile, according to the class teacher, the physical activity of elementary school children according to the class teacher has not met the adequacy criteria set.